KLAUSULA BAKU DALAM BIDANG PERUMAHAN - Yudha Hadian Nur; Ratna Anita Carolina (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2010)
Standard agreement is one of the instruments used in the business that aim to improve the efficiency and effectiveness of transactions conducted between businesses and consumers. But the problem that often occurs is the standard agreement does not reflect a balanced position between businesses and consumers. In line with this problem, this study aims to identify deviations to the provisions of Article 18 of Consumer Protection Law on standard clauses, particularly in the housing sector, and identify consumer understanding of the existence of standard clauses and the impact after the signing the sale purchase agreement (PPJB) of house. This study was conducted in five regions namely Jabodetabek, Bandung, Surabaya, Batam and Makassar. The analytical method used collecting data the depth interviews with stakeholders, analysis of the contents of the PPJB document, and the descriptive analysis of the survey to the consumer respondents. The results of this study show that in general, there are several housing developers who include standard clauses that are prohibited in the PPJB of house and other documents which are an integral part of the PPJB. In addition, the analysis also show that although the consumer has read the PPJB document, the average consumer does not understand the intent of these agreements. This is due to the bonafides developers and confidence to the developers. Based on that problem, it is needed to increased sosialization of the rights and obligations of the consumers and businessmen to create the conducive business climate in the context of consumer protection.